2012
DOI: 10.1007/s10549-011-1949-5
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of reduced chemotherapy relative dose intensity among women with early stage breast cancer in US clinical practice

Abstract: Chemotherapy is widely used to treat early stage breast cancer (ESBC). Reductions and delays in dose administered--e.g., due to advanced age or febrile neutropenia (FN)--are generally believed to increase risk of disease progression and reduce survival. Little is known about incidence of reduced chemotherapy dose intensity among women with ESBC in the current era of US clinical practice. This study employed a retrospective cohort design and electronic medical records from > 65 community oncology/hematology cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
43
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 16 publications
2
43
1
Order By: Relevance
“…Widespread screening programs have contributed to its early diagnosis and the current standard treatment for early-stage breast cancer (ESBC) is surgery followed by local radiation therapy and systemic adjuvant treatments using chemotherapy and/or hormonal agents. Advances in systemic adjuvant chemotherapy have shown several convincing roles in preventing relapse and extending survival [3,4]. The dose of adjuvant chemotherapy is known to be one of the important variables that affect the ability of patients with ESBC to achieve maximal benefit [5,6,7,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Widespread screening programs have contributed to its early diagnosis and the current standard treatment for early-stage breast cancer (ESBC) is surgery followed by local radiation therapy and systemic adjuvant treatments using chemotherapy and/or hormonal agents. Advances in systemic adjuvant chemotherapy have shown several convincing roles in preventing relapse and extending survival [3,4]. The dose of adjuvant chemotherapy is known to be one of the important variables that affect the ability of patients with ESBC to achieve maximal benefit [5,6,7,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…The outcomes of subjects with doses lower than 85% of RDI were reported to be similar to the outcomes of subjects treated with surgery alone (7,8). In fact, a retrospective cohort study has demonstrated that chemotherapy dose delays and dose reductions are common among breast cancer patients receiving conventional chemotherapy regimens in approximately 20% of cases (9,10).…”
Section: Introductionmentioning
confidence: 82%
“…Nevertheless, RDI reductions are common in clinical practice, and a large nationwide study of community practices identified RDI reductions of 15% or more in over half of patients with early-stage breast cancer [29]. Across several studies, advanced age has consistently been found to be a risk factor for a decreased RDI, and older women with breast cancer are more likely to have a reduced RDI compared with younger women [2, 3034]. …”
Section: Discussionmentioning
confidence: 99%